Zenker’s peroral endoscopic myotomy for management of large Zenker’s diverticulum - Zhang, Linda Y.; Hernández Mondragón, Oscar; Pioche, Mathieu; Steinway, Steven N.; Nieto, Jose; Ujiki, Michael B.; VanDruff, Vanessa N.; Kim, Raymond E.; Canakis, Andrew; Tantau, Marcel; Tantau, Alina; Pop, Anamaria; Jacques, Jérémie; Lajin, Michael; Desai, Pankaj; Shrigiriwar, Apurva; Bejjani, Michael; Kumta, Nikhil A.; Khashab, Mouen A. (Endoscopy, 2023)
Background Zenker’s diverticulum peroral endoscopic myotomy (zPOEM) is a minimally invasive treatment strategy for Zenker’s diverticulum, with excellent results for management of small-to-moderate Zenker’s diverticulum. We evaluated its use in the management of large Zenker’s diverticulum.Methods This was a retrospective multicenter cohort study across 11 international centers including adult patients with large Zenker’s diverticulum ≥ 40 mm treated by zPOEM between March 2017 and March 2022. The primary outcome was clinical success (dysphagia score ≤ 1 without need for further intervention). Secondary outcomes included technical success (complete myotomy as intended), adverse events (AEs), and rate of recurrence.Results 83 patients (male 62.7 %, mean age 72.6 [SD 11.5] years) underwent zPOEM for treatment of large Zenker’s diverticulum (median size 50 mm, interquartile range [IQR] 41–55 mm, range 40–80 mm). The zPOEM procedure was technically successful in 82 patients (98.8 %), with a mean procedure time of 48.7 (SD 23.2) minutes. Clinical success was achieved in 71 patients (85.5 %). Median (IQR) symptom scores improved significantly from baseline for dysphagia (2 23 vs. 0 [0–2]; P < 0.001), regurgitation (3 234 vs. 0 [0–0]; P < 0.001), and respiratory symptoms (2 [0–3] vs. 0 [0–0]; P < 0.001). Among patients achieving clinical success, only one recurrence (1.4 %) was recorded during a median follow-up of 12.2 months (IQR 3–28). Post-procedure AEs, all mild to moderate, occurred in four patients (4.8 %).Conclusion: This study demonstrated safe and effective use of zPOEM in the management of large Zenker’s diverticulum.